Acute hemorrhagic encephalomyelitis - Rare presentation of pediatric multisystem inflammatory syndrome temporally associated with SARS-CoV-2: A case report - Prasanna Narayanan Raju; Pradheep Subramanian Raju; Muthukumaran Pooranalingam; Raju Subramanian (Wolters Kluwer Medknow Publications, 2021)
Acute hemorrhagic encephalomyelitis (AHEM) is a rare form of acute disseminated encephalomyelitis (ADEM) characterized by a fulminant course, poor response to immunomodulation, and unfavorable outcomes. Early clinical and radiological suspicion can enable aggressive use of immunotherapy, thereby improving outcomes. Pediatric multisystem inflammatory syndrome temporally associated with SARS-CoV-2 (PIMS-TS) is a novel disease, with protean clinical manifestations being reported from all over the world. Although multiple neurological manifestations of PIMS-TS have been reported previously, AHEM has been less commonly reported. We describe a case of PIMS-TS with AHEM and highlight very rare presentation of this novel disease.